ORAL ERYTHEMA MULTIFORME â€“ CASE REPORTS, DIAGNOSTIC AND TREATMENT DILEMMA - Belazelkovska Grezhlovska, Ana; Nikolovski, Bruno; Radojkova Nikolovska, Vera (Journal of Morphological Sciences; Vol 5 No 2 (2022): JMS, 2022)
Erythema multiforme is acute mucocutaneous condition that is considered to be immune- mediated hypersensitivity reaction to medicine or an infection. There are described three forms of erythema multiforme: â€œminor formâ€, â€œmajor formâ€ and oral erythema multiforme. It presents  a diagnostic dilemma due to varied possible manifestations. Diagnosis is often made based on history and clinical examination. In this article we report 5 cases of different forms of erythema multiforme following drug administration. Keywords: erythema multiforme, drug induced.